Electrochemical device and electronic device comprising same
By using fluorovinyl carbonate and SO2F-general compounds to form a stable inorganic SEI film and passivation layer in lithium-ion batteries, the electrolyte consumption and active lithium loss caused by excessive reactivity after lithiation of silicon-based materials is solved. Problem, the cycle performance and energy density of the battery are significantly improved.
Patent Information
- Application Number
- CN202411207751.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-07
AI Technical Summary
The lithium silicon alloy formed by silicon-based materials after lithiation in lithium-ion batteries is highly reactive, resulting in rapid consumption of electrolyte and loss of active lithium, affecting the battery circulation performance.
Add fluorovinyl carbonate (FEC) and SO2F-general compound of specific compounds to the electrolyte to form a stable inorganic SEI film, preventing the excessive polymerization of FEC, and forming lithium-containing materials rich in S and F elements at the electrode interface The passivation layer of inorganic compounds coordinates to form a thinner solid electrolyte interface film, improving the cycling performance of the electrochemical device.
It effectively reduces the consumption rate of FEC, improves the cycle stability and energy density of the battery, and improves the cycle performance of the electrochemical device.
Smart Images

Figure CN119275345A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to an electrochemical device and an electronic device comprising the electrochemical device. Background Art
[0002] With the rapid development of electronic products, secondary batteries are widely used in mobile phones, laptops, tablets, drones, electric vehicles, power tools, power storage systems, etc. due to their advantages such as high energy density, miniaturization and lightweight. Especially in the field of 3C products, consumer users still have great demand for improving the battery life of electronic products, so higher requirements are placed on the energy density of secondary batteries. In order to further improve the energy density of secondary batteries, it is necessary to use electrode materials with high specific capacity. As a type of alloyed negative electrode material, silicon-based materials can provide an ultra-high specific capacity of up to 4200mAh / g, so silicon-based materials are materials with great potential for improving energy density. However, after lithium-based materials are lithiated, lithium-silicon alloys will be formed. Lithium-silicon alloys have highly active reactivity and are extremely easy to attack solvent molecules in the electrolyte, resulting in rapid consumption of the electrolyte and loss of active lithium, so there will be problems with poor cycle performance. Summary of the invention
[0003] The purpose of the present application is to provide an electrochemical device and an electronic device to improve the cycle performance of the electrochemical device.
[0004] The first aspect of the present application provides an electrochemical device, which includes a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes silicon element, and based on the total mass of the negative electrode material layer, the mass percentage content A of the silicon element is 1% to 20%;
[0005] The electrolyte comprises a compound of formula I and fluoroethylene carbonate:
[0006]
[0007] wherein R is selected from unsubstituted or fluorine-substituted C 2 -C 6 Alkyl, unsubstituted or fluorinated C 6 -C 12 Aryl;
[0008] Based on the total mass of the electrolyte, the mass percentage C of the compound of formula I is 3% to 50%.
[0009] In one embodiment of the present application, the compound of formula I is selected from at least one of the following compounds:
[0010]
[0011]
[0012] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage B of fluoroethylene carbonate is 5% to 30%.
[0013] In one embodiment of the present application, the relationship between the mass percentage content B of fluoroethylene carbonate and the mass percentage content A of silicon element satisfies 1≤B / A≤10.
[0014] In one embodiment of the present application, the relationship between the mass percentage C of the compound of formula I and the mass percentage A of silicon element satisfies 1≤C / A≤10.
[0015] In one embodiment of the present application, the electrolyte further includes a non-fluorinated cyclic carbonate, and the non-fluorinated cyclic carbonate includes at least one of ethylene carbonate or propylene carbonate; based on the total mass of the electrolyte, the mass percentage of the non-fluorinated cyclic carbonate is 10% to 30%.
[0016] In one embodiment of the present application, the electrolyte includes linear carbonate, and the linear carbonate includes at least one of ethyl methyl carbonate or diethyl carbonate; based on the total mass of the electrolyte, the mass percentage of the linear carbonate is 5% to 40%.
[0017] In one embodiment of the present application, the electrolyte further comprises linear carboxylates, which include at least one of ethyl propionate, propyl acetate, propyl propionate, butyl acetate, ethyl butyrate or ethyl isobutyrate; based on the total mass of the electrolyte, the mass percentage of the linear carboxylate is 5% to 40%.
[0018] In one embodiment of the present application, the electrolyte includes a lithium salt additive, and the lithium salt additive includes at least one of lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide or lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of the lithium salt additive is 0.1wt% to 5wt%.
[0019] In one embodiment of the present application, the electrochemical device includes an isolation membrane, and along the direction in which the electrode ear of the electrochemical device extends, the length of the isolation membrane extending beyond the positive electrode plate is a μm, the thickness of the isolation membrane is b μm, 0.0008≤b / a≤0.018, and a satisfies the condition: 1000≤a≤5000.
[0020] A second aspect of the present application provides an electronic device, which includes the electrochemical device provided by the first aspect of the present application.
[0021] Beneficial effects of this application:
[0022] The present application provides an electrochemical device, which includes a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes silicon element, and the mass percentage A of the silicon element is 1% to 20% based on the total mass of the negative electrode material layer; and the electrolyte includes a compound of formula I and fluoroethylene carbonate (Fluoroethylene carbonate, FEC). Among them, FEC is a good electrolyte additive for electrochemical devices. During the formation process, the FEC in the electrolyte can form a cross-linked high-toughness polymer protective layer at the electrode interface, thereby greatly improving the cycle performance of the electrochemical device, but the consumption rate of FEC is fast, and the polymer layer formed is thick, which will hinder the transmission of lithium ions. By adding the compound of formula I, a positive and negative electrode interface passivation layer of a lithium-containing inorganic compound rich in S and F elements is formed at the electrode interface, thereby preventing excessive polymerization of FEC, thereby synergistically forming a thinner solid electrolyte interface film (solid electrolyte interface, SEI) / positive electrode electrolyte interface layer (Cathode Electrolyte Interface, CEI), thereby improving the cycle performance of the electrochemical device.
[0023] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0025] In order to solve the problem of rapid consumption of electrolyte and loss of active lithium in silicon-based battery, FEC is usually added in the prior art. FEC is an excellent film-forming additive used to repair the damage of SEI film on the surface of silicon particles. However, the consumption rate of FEC is fast, and excessive addition of FEC will lead to poor battery cycle performance. Therefore, the present invention adds SO 2 The compound of the general formula F- is used to construct a Li-containing 2 The SEI film of inorganic components such as S and LiF has a more stable inorganic phase film formation and can promote ion transport, thereby improving the stability of the overall SEI film, reducing the consumption rate of FEC, and improving the cycle stability of the electrochemical device.
[0026] It should be noted that in the specific embodiments of the present application, lithium-ion batteries are used as an example of electrochemical devices to explain the present application, but the electrochemical devices of the present application are not limited to lithium-ion batteries. The electrochemical devices of the present application are not particularly limited and may include any device that undergoes electrochemical reactions.
[0027] The first aspect of the present application provides an electrochemical device, which includes a negative electrode plate and an electrolyte, wherein the negative electrode plate includes a negative electrode material layer, the negative electrode material layer includes silicon element, and based on the total mass of the negative electrode material layer, the mass percentage content A of the silicon element is 1% to 20%; the electrolyte includes a compound of formula I and fluoroethylene carbonate:
[0028]
[0029] wherein R is selected from unsubstituted or fluorine-substituted C 2 -C 6 Alkyl, unsubstituted or fluorinated C 6 -C 12 Aromatic group; based on the total mass of the electrolyte, the mass percentage C of the compound of formula I is 3% to 50%. The mass percentage A of the silicon element is controlled within the above range, so that during the charging and discharging process of the electrochemical device, the space required for the expansion of the nano-silicon particles can be met, thereby effectively alleviating the phenomenon of material rupture caused by the expansion of the nano-silicon particles, and improving the energy density and cycle performance of the electrochemical device. However, in the electrochemical device containing silicon-based materials, the lithium alloy formed after the silicon-based materials are lithiated has a highly active reactivity, resulting in rapid consumption of the electrolyte, thereby affecting the cycle performance of the electrochemical device. In the present application, the compound of formula I and FEC are added to the electrolyte at the same time, and the mass percentage C of the compound of formula I is controlled within the above range, and a positive and negative electrode interface passivation layer of a lithium-containing inorganic compound rich in S and F elements can be formed at the electrode interface, thereby preventing the excessive polymerization of FEC, thereby synergistically forming a thinner SEI / CEI layer, achieving the reduction of FEC consumption and loss of active lithium, and improving the cycle performance of the electrochemical device.
[0030] The negative electrode material layer contains silicon element, and based on the total mass of the negative electrode material layer, the mass percentage A of the silicon element is 1% to 20%, for example, it can be 1%, 5%, 10%, 15%, 20% or a range consisting of any two values therein. The silicon element is introduced by a silicon-based material, and the silicon-based material can be selected from at least one of a silicon-carbon material, a silicon-oxygen material or micron silicon.
[0031] The negative electrode material layer also includes a carbon material, which may include at least one of natural graphite, artificial graphite, hard carbon material, soft carbon material or mesophase microcarbon spheres, and the content of the carbon material ranges from 30% to 60%. For example, it may be 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two of these values.
[0032] Based on the mass of the electrolyte, the mass percentage C of the compound of formula I is 3% to 50%, for example, it can be 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two values therein. When the content of the compound of formula I is too little, the lithium-containing inorganic substances rich in S and F elements formed at the electrode interface are not enough to regulate the decomposition of FEC, and the strength is insufficient; when the compound of formula I is more, the content of lithium-containing inorganic substances rich in S and F elements formed at the electrode interface is too much, resulting in excessive rigidity and brittleness of SEI. By controlling the mass percentage C of the compound of formula I within the above range, the decomposition product of the compound of formula I is an inorganic-rich phase, which can match the organic phase formed by FEC, achieving an effect similar to that of a polymer / inorganic composite solid electrolyte, with higher stability, thereby improving the cycle performance of the electrochemical device.
[0033] In one embodiment of the present application, the compound of formula I is selected from at least one of the following compounds:
[0034]
[0035]
[0036] An electrolyte comprising at least one of the compounds of formula I is applied to an electrochemical device. The decomposition product of the compound of formula I is an inorganic-rich phase, which can match the organic phase formed by FEC, thereby achieving an effect similar to that of a polymer / inorganic composite solid electrolyte, having higher stability, reducing the consumption of FEC and the loss of active lithium without affecting other properties, and improving the cycle performance of the electrochemical device.
[0037] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage B of fluoroethylene carbonate is 5% to 30%. For example, B can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two values therein. By controlling the mass percentage B of fluoroethylene carbonate within the above range, FEC can form a cross-linked, high-toughness polymer protective layer at the electrode interface during the battery formation process, thereby greatly improving the cycle performance of the lithium secondary battery. If the FEC content is too low, it is difficult to form a complete polymer layer, and the cycle performance of the electrochemical device is poor; if the content is too high, an overly thick polymer layer is formed at the electrode interface, resulting in obstruction of interfacial ion transport, and poor low temperature and rate discharge of the electrochemical device.
[0038] In one embodiment of the present application, the relationship between the mass percentage content B of fluoroethylene carbonate and the mass percentage content A of silicon element satisfies 1≤B / A≤10. For example, the value of B / A can be 1, 3, 5, 8, 10 or a range consisting of any two of these values. By regulating the ratio of the mass percentage content B of fluoroethylene carbonate to the mass percentage content A of silicon element within the above range, the SEI film under the volume expansion of Si can be repaired and the cycle performance of the electrochemical device can be improved.
[0039] In one embodiment of the present application, the relationship between the mass percentage content C of the compound of formula I and the mass percentage content A of the silicon element satisfies 1≤C / A≤10. For example, the value of C / A can be 1, 3, 5, 8, 10 or a range consisting of any two of the values. By regulating the ratio of the mass percentage content C of the compound of formula I to the mass percentage content A of the silicon element within the above range, it can effectively play the role of passivating the interface and improve the cycle performance of the electrochemical device.
[0040] In one embodiment of the present application, the electrolyte further comprises a non-fluorinated cyclic carbonate, and the non-fluorinated cyclic carbonate comprises at least one of ethylene carbonate or propylene carbonate; based on the total mass of the electrolyte, the mass percentage of the non-fluorinated cyclic carbonate is 10% to 30%. For example, the mass percentage of the non-fluorinated cyclic carbonate can be 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the values. By controlling the mass percentage of the non-fluorinated cyclic carbonate within the above range, the electrolyte ion transport performance, the electrochemical device interface impedance and the cycle performance of the electrochemical device can be improved.
[0041] In one embodiment of the present application, the electrolyte includes a linear carbonate, and the linear carbonate includes at least one of ethyl methyl carbonate or diethyl carbonate; based on the total mass of the electrolyte, the mass percentage of the linear carbonate is 5% to 40%. By selecting at least one of the above materials, the mass percentage is controlled within the above range, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or a range consisting of any two of the values. The linear carbonate has a low viscosity, and adding it to the electrolyte will improve the overall ionic conductivity.
[0042] In one embodiment of the present application, the electrolyte further comprises a linear carboxylate, which comprises at least one of ethyl propionate, propyl acetate, propyl propionate, butyl acetate, ethyl butyrate or ethyl isobutyrate; based on the total mass of the electrolyte, the mass percentage of the linear carboxylate is 5% to 40%. By selecting at least one of the above materials and controlling the mass percentage within the above range, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or a range consisting of any two of the values, the overall ionic conductivity and kinetic performance of the electrochemical device can be further improved.
[0043] In one embodiment of the present application, the electrolyte includes a lithium salt additive, and the lithium salt additive includes at least one of lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, or lithium (fluorosulfonyl) (trifluoromethanesulfonyl) imide; based on the total mass of the electrolyte, the mass percentage of the lithium salt additive is 0.1wt% to 5wt%. By selecting at least one of the above materials, the mass percentage of the lithium salt additive is controlled within the above range, for example, the mass percentage of the lithium salt additive can be 0.1wt%, 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt%, 5.0wt%, or a range consisting of any two of the values, combined with LiPF 6 Main salt, which can improve the cycling performance of electrochemical devices.
[0044] In the present application, the electrolyte also includes a non-aqueous solvent. The non-aqueous solvent includes dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, caprolactone, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate and combinations thereof.
[0045] The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, the mass percentage of the non-aqueous solvent in the base electrolyte is 0% to 73.9%, for example, the mass percentage of the non-aqueous solvent can be 0%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 73.9% or a range consisting of any two of these values.
[0046] In the present application, the electrolyte further comprises a lithium salt, and the lithium salt is not particularly limited, and any lithium salt known in the art can be used as long as the purpose of the present application can be achieved. For example, the lithium salt can be selected from LiPF 6 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 and LiC( 8 O 2 CF 3 ) 3 For example, the lithium salt may be LiPF 6 For example, based on the mass of the electrolyte, the mass percentage of the lithium salt may be 8% to 20%, for example, the mass percentage of the lithium salt may be 8%, 10%, 12%, 13%, 15%, 18%, 20% or a range consisting of any two of these values.
[0047] In one embodiment of the present application, the length of the separator extending along the direction of the tab of the electrochemical device beyond the positive electrode is a μm, the thickness of the separator is b μm, 0.0008≤b / a≤0.018, and a satisfies the condition: 1000≤a≤5000. For example, the length of the separator extending beyond the positive electrode is a μm, which can be 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, or a range consisting of any two of the values; the ratio b / a of the thickness of the separator is b μm and the length of the separator extending along the direction of the tab of the electrochemical device beyond the positive electrode is a μm can be 0.0008, 0.001, 0.005, 0.01, 0.012, 0.015, 0.018, or a range consisting of any two of the values. By controlling the length a of the separator beyond the positive electrode sheet within the above range, short circuits between the positive and negative electrodes can be avoided, while also ensuring that the space of the electrochemical device is not wasted, thereby causing a loss in the mass energy density (ED) of the electrochemical device; the ratio of the thickness bμm of the separator and the length aμm beyond the positive electrode sheet can be controlled within the above range, which can reduce the loss of the energy density of the electrochemical device while ensuring the mechanical properties of the electrochemical device; in the electrolyte, FEC itself improves the thermal shock resistance of the separator, and the addition of at least one compound of formula I can further enhance this effect, reduce the increase in the internal temperature of the electrochemical device under high-temperature abuse, and reduce the shrinkage of the separator. In the present application, the length aμm of the separator beyond the positive electrode sheet, and the ratio of the thickness bμm of the separator to the length aμm of the separator beyond the positive electrode sheet are most consistent with the requirements of the energy density and stability of the electrochemical device within the protection scope of the present application.
[0048] The present application has no other restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the isolation membrane may include at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid, etc. Polyethylene and polypropylene can prevent short circuits and improve the stability of electrochemical devices through the shutdown effect. For example, polyethylene may include at least one of high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. The surface of the isolation membrane may include a porous layer, and the porous layer is disposed on at least one surface of the isolation membrane. The porous layer may include at least one of inorganic particles or a binder. The porous layer can enhance the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the pole piece. For example, the inorganic particles may include aluminum oxide (Al 2 O 3 ), silicon oxide (SiO), magnesium oxide (MgO), titanium oxide (TiO 2 ), hafnium dioxide (HfO 2 ), tin oxide (SnO 2 ), cerium dioxide (CeO2 ), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO 2 ), yttrium oxide (Y 2 O 3 ), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate, etc. For example, the binder of the porous layer may include at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene, etc. In the present application, the thickness of the isolation film can be any thickness as long as it can achieve the purpose of the present application, for example, the thickness of the isolation film can be 4μm to 30μm.
[0049] The present application has no special restrictions on the positive electrode plate, as long as the purpose of the present application can be achieved. For example, the positive electrode plate includes a positive current collector and a positive electrode material layer arranged on at least one surface of the positive current collector. The present application has no special restrictions on the positive current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The positive electrode material layer includes a positive electrode active material. The present application has no special restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO 2 ), at least one of lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0050] The cathode material layer of the present application may also include a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, lamellar graphite, graphene, carbon nanotubes, carbon nanowires or carbon fibers. The binder may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, sodium carboxymethyl cellulose (CMC-Na), polyvinyl acetate, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyaniline, polyimide, polyamide-imide, polysiloxane, epoxy resin, polyester resin, polyurethane resin or polyfluorene, etc. At least one.
[0051] The present application has no particular restrictions on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode material layer is 30 μm to 120 μm.
[0052] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, for example, it can be at least one of the above conductive agent and the above binder.
[0053] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.
[0054] In some embodiments of the present application, the negative electrode material layer may further include a conductive agent, a binder and a thickener. The present application does not particularly limit the types of the conductive agent and the thickener, as long as the purpose of the present application can be achieved. For example, the conductive agent and the binder may be at least one of the above conductive agent and the above binder. The thickener may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener in the negative electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0055] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 150 μm.
[0056] The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0057] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, and it may be at least one of the above conductive agent and the above binder.
[0058] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the electrochemical device from rising and overcharging and discharging. The present application does not limit the packaging bag, and those skilled in the art may select it according to actual needs, as long as the purpose of the present application can be achieved. For example, an aluminum-plastic film packaging bag may be used.
[0059] The second aspect of the present application provides an electronic device, which includes the electrochemical device provided in the first aspect of the present application,
[0060] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium-ion capacitor, etc.
[0061] Example
[0062] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0063] Test methods and equipment:
[0064] Test of silicon mass percentage:
[0065] The lithium-ion battery discharged at 0.5C to 3.0V was disassembled, the negative electrode plate was removed, and it was soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. Then the negative electrode plate was placed in an oven and baked at 80°C for 12 hours to obtain the negative electrode plate. The negative electrode plate was placed in a vacuum oven and dried at 100°C for 24 hours, and 1g of the powdered sample of the negative electrode material layer on the negative electrode plate was scraped off with a blade, and then the mass percentage of silicon element in the negative electrode material layer was tested using an ICP (Inductively coupled plasma) analyzer.
[0066] Cycle performance test:
[0067] Place the lithium-ion battery in a 25℃ constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.45V at a constant current of 0.5C, then charge it at a constant voltage to a current of 0.025C, let it stand for 5 minutes, and discharge it to 3.0V at a constant current of 0.5C. Record it as the initial discharge capacity C 1 Repeat this procedure for 200 cycles and record the discharge capacity C after 200 cycles. 2 , calculate the cycle capacity retention rate of lithium-ion batteries. Cycle capacity retention rate = C 2 / C 1 ×100%.
[0068] Cyclic thickness growth rate test:
[0069] Charge at a constant current of 0.5C to 4.45V, then charge at a constant voltage to a current of 0.025C, let stand for 5 minutes, measure the thickness, and count it as the thickness of the battery when it is fully charged for the first time; use the same charge and discharge process as in the above-mentioned cycle capacity retention test, cycle 500 times, measure the thickness, and count it as the battery thickness after the 500th cycle.
[0070] The difference between the battery thickness after the 500th cycle and the thickness of the battery when it is fully charged for the first time is divided by the thickness of the battery when it is fully charged for the first time. The battery thickness is measured with a micrometer, and 5 measurements are taken at 5 different positions to take the average value, which is the cycle thickness growth rate. The smaller the cycle thickness growth rate, the better.
[0071] Example 1-1
[0072] <Preparation of positive electrode sheet>
[0073] The positive electrode active material lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2.5:2.5, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75%, and stirred evenly. The slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10 μm, and dried at 90°C to obtain a positive electrode sheet with a coating thickness of 110 μm. After the above steps are completed, the single-sided coating of the positive electrode sheet is completed. After that, the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with double-sided coating of positive electrode active materials. After the coating is completed, the positive electrode sheet is cut into a specification of 74mm×867mm and welded to the pole ear for standby use.
[0074] <Preparation of negative electrode sheet>
[0075] Si / C composite material (carbon nanopore loaded Si), artificial graphite, negative electrode binder lithium polyacrylate (PAA-Li), and negative electrode conductive agent carbon nanotubes are mixed in a mass ratio of 20:70:7:3, deionized water is added, and the mixture is evenly mixed under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 30wt%. The negative electrode slurry is evenly coated on one side of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided negative electrode material layer coated with a coating thickness of 143μm, and then the above steps are repeated on the other side of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer coated, and then cold pressed and cut to obtain a negative electrode sheet with a specification of 78mm×875mm. Among them, based on the total mass of the negative electrode material layer, the mass percentage of Si element is 10%. The thickness of the single-sided negative electrode material layer after cold pressing is 80μm.
[0076] <Preparation of Electrolyte>
[0077] In an argon atmosphere glove box with a water content of <10ppm>, dimethyl carbonate and ethyl acetate are mixed in a mass ratio of 1:1 to obtain a basic solvent, and then fluoroethylene carbonate, a compound of formula I-2 and lithium hexafluorophosphate are added and mixed uniformly to obtain an electrolyte. Wherein, based on the mass of the electrolyte, the mass percentage of lithium hexafluorophosphate is 12.5%, the mass percentage of fluoroethylene carbonate is 20%, the mass percentage of the compound of formula I-2 is 3%, and the balance is the basic solvent.
[0078] <Preparation of Separator Film>
[0079] A polyethylene (PE) film with a thickness of 15 μm (provided by Celgard) was used.
[0080] <Preparation of lithium-ion batteries>
[0081] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, so that the separator is located between the positive electrode and the negative electrode to play a role of isolation, and then wound to obtain an electrode assembly. Along the extension direction of the electrode ear of the electrochemical device, the length of the separator beyond the positive electrode sheet is 5 mm, and the thickness of the separator is 15 μm. The electrode assembly is placed in an aluminum-plastic film packaging bag, and after drying, the electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, degassing, trimming and other processes.
[0082] Among them, based on the total mass of the negative electrode material layer, the mass percentage of silicon element is 10%; based on the total mass of the electrolyte, the mass percentage of the compound of formula I is 3%, and the mass percentage of fluoroethylene carbonate is 20%, as shown in Table 1. The less than 100% is supplemented with a basic solvent.
[0083] Example 1-2 to Example 1-8
[0084] Except that the mass percentage of the compound of formula I-2 and fluoroethylene carbonate is adjusted according to Table 1 in <Preparation of electrolyte>, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-1.
[0085] Example 1-9 to Example 1-10
[0086] Except that the parameters related to the mass percentage of silicon element in the negative electrode material layer are adjusted according to Table 1 in the preparation of the negative electrode plate, the rest are the same as those in Example 1-3.
[0087] Example 1-11 to Example 1-14
[0088] Except that the parameters related to the type of compound of formula I in <Preparation of electrolyte> are adjusted according to Table 1, the rest are the same as Examples 1-3.
[0089] Comparative Example 1
[0090] Except that the compound of formula I-2 is not added according to Table 1 in <Preparation of electrolyte>, the mass percentage of the basic solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-3.
[0091] Comparative Example 2
[0092] Except that FEC is not added in <Preparation of Electrolyte> according to Table 1, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-3.
[0093] Comparative Examples 3 to 6
[0094] Except that the mass percentage of the compound of formula I-2 and fluoroethylene carbonate is adjusted according to Table 1 in <Preparation of electrolyte>, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-3.
[0095] Example 2-1
[0096] Except that the relevant parameters of propylene carbonate were added according to Table 2 in <Preparation of Electrolyte>, the mass percentage of the base solvent was changed accordingly, and the mass percentage of the lithium salt remained unchanged, the rest was the same as Example 1-7.
[0097] Example 2-2 to Example 2-4
[0098] Except that the mass percentage of propylene carbonate and related parameters in <Preparation of Electrolyte> are adjusted according to Table 2, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 2-1.
[0099] Example 2-5 to Example 2-6
[0100] Except that the parameters related to the type of non-fluorinated cyclic carbonate in <Preparation of Electrolyte> are adjusted according to Table 2, the rest are the same as Example 2-3.
[0101] Embodiment 2-7
[0102] Except that the relevant parameters of ethyl methyl carbonate were added according to Table 2 in <Preparation of Electrolyte>, the mass percentage of the base solvent was changed accordingly, and the mass percentage of the lithium salt remained unchanged, the rest was the same as Example 1-7.
[0103] Example 2-8 to Example 2-10
[0104] Except that the mass percentage of ethyl methyl carbonate and related parameters in <Preparation of Electrolyte> are adjusted according to Table 2, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 2-7.
[0105] Example 2-11
[0106] Except that the parameters related to the type of linear carbonate in <Preparation of Electrolyte> are adjusted according to Table 2, the rest are the same as Example 2-8.
[0107] Example 2-12
[0108] Except that the relevant parameters of propyl propionate were added according to Table 2 in <Preparation of Electrolyte>, the mass percentage of the base solvent was changed accordingly, and the mass percentage of the lithium salt remained unchanged, the rest was the same as Example 1-7.
[0109] Example 2-13 to Example 2-15
[0110] Except that the mass percentage of propyl propionate is adjusted according to Table 2 in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 2-12.
[0111] Example 2-16
[0112] Except that the parameters related to the type of linear carboxylic acid ester are adjusted according to Table 2 in <Preparation of Electrolyte>, the rest are the same as Example 2-13.
[0113] Example 2-17 to Example 2-20
[0114] Except that the mass percentage of propylene carbonate, ethylene carbonate, ethyl methyl carbonate and propyl propionate is adjusted according to Table 2 in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-7.
[0115] Example 3-1 to Example 3-3
[0116] Except that the mass percentage of the lithium salt additive is adjusted according to Table 3 in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-3.
[0117] Example 3-4 to Example 3-5
[0118] Except that the number of types of lithium salt additives and the mass percentage related parameters of the lithium salt additives are adjusted according to Table 3 in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 1-3.
[0119] Example 3-6 to Example 3-8
[0120] Except that the number of types and mass percentage of lithium salt additives and related parameters of lithium salt additives are adjusted according to Table 3 in <Preparation of Electrolyte>, the mass percentage of the base solvent is changed accordingly, and the mass percentage of the lithium salt remains unchanged, the rest is the same as Example 2-17.
[0121] Example 4-1 to Example 4-5
[0122] Except that the parameters of the length aμm and thickness bμm of the isolation membrane extending beyond the positive electrode sheet are adjusted according to Table 4 in <Preparation of Lithium-ion Batteries>, and the ratio (b / a) of the thickness bμm of the isolation membrane to the length aμm extending beyond the positive electrode sheet is changed accordingly, the rest is the same as Examples 1-3.
[0123] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 4.
[0124] Table 1
[0125]
[0126]
[0127] Note: “ / ” in Table 1 indicates that there is no corresponding preparation parameter, substance or performance parameter.
[0128] From Example 1-1 to Example 1-14 and Comparative Example 1 to Comparative Example 6, it can be seen that the examples select the type of compound of formula I within the protection scope of the present application, and adjust the mass percentage C, the mass percentage B of fluoroethylene carbonate, and the mass percentage A of silicon, while the comparative examples do not meet the above characteristics at the same time. In the examples of the present application, the lithium ion battery has a higher capacity retention rate and a lower cycle thickness growth rate, indicating that the lithium ion battery has better cycle performance.
[0129] In the electrolyte, the mass percentage C of the compound of formula I usually affects the cycle performance of the electrochemical device. From Example 1-1 to Example 1-5, Comparative Example 1, Comparative Example 3, and Comparative Example 4, it can be seen that when C is too large, such as Comparative Example 4, the capacity retention rate of the lithium-ion battery is low and the cycle thickness growth rate is high; when C is too small, such as Comparative Example 3, the capacity retention rate of the lithium-ion battery is low and the cycle thickness growth rate is high; when the compound of formula I is not included, such as Comparative Example 1, the cycle thickness growth rate of the lithium-ion battery is high, indicating that the value of C is too large or too small, and the cycle performance of the lithium-ion battery cannot be improved. Therefore, by regulating the value of C within the scope of protection of this application, the decomposition product of the compound of formula I is an inorganic-rich phase, which can match the organic phase formed by FEC, reduce the gas production generated by the oxidation reaction, and make the lithium-ion battery have a higher capacity retention rate and a lower cycle thickness growth rate, indicating that the lithium-ion battery has better cycle performance.
[0130] In the electrolyte, the type of compound of formula I usually affects the cycle performance of the electrochemical device. From Examples 1-11 to 1-14, it can be seen that by selecting the compound of formula I within the protection scope of the present application, the capacity retention rate of the lithium ion battery is higher and the cycle thickness growth rate is lower, indicating that the lithium ion battery has better cycle performance.
[0131] In the electrolyte, the mass percentage content B of FEC usually affects the cycle performance of the electrochemical device. From Examples 1-3, Examples 1-6 to Examples 1-8, Comparative Examples 2 to Comparative Examples 3, and Comparative Example 4, it can be seen that when B is too large, such as Comparative Example 4, the cycle performance of the lithium-ion battery is poor, FEC is oxidized on the positive electrode side to generate carbon dioxide, and the cycle thickness growth rate is high; when B is too small, such as Comparative Example 3, the cycle performance of the lithium-ion battery is poor, and the cycle thickness growth rate is low; when FEC is not included in the electrolyte, such as Comparative Example 2, the cycle performance of the lithium-ion battery is even worse, indicating that when B is too large or too small, the cycle performance of the lithium-ion battery cannot be improved. Therefore, by adjusting the value of B within the protection scope of this application, the lithium-ion battery can have a higher capacity retention rate and a lower cycle thickness growth rate, indicating that the lithium-ion battery has better cycle performance.
[0132] Table 2
[0133]
[0134]
[0135] Note: “\” in Table 2 indicates that there is no corresponding preparation parameter, substance or performance parameter.
[0136] The composition and content of the electrolyte usually affect the cycle performance of the lithium-ion battery. Through Examples 2-1 to 2-20, when the composition and content of the electrolyte are within the protection scope of the present application, the lithium-ion battery has better cycle performance.
[0137] In the electrolyte, the type and mass percentage of non-fluorinated cyclic carbonates usually affect the cycle performance of the electrochemical device. It can be seen from Examples 2-1 to 2-4 that within the scope of protection of the present application, the addition of propylene carbonate to the electrolyte can enhance interfacial ion transport, improve interfacial film stability, improve the capacity retention rate of the electrochemical device, and reduce the cycle thickness growth rate as the mass percentage increases; in Examples 2-5 to 2-6, the addition of at least one of ethylene carbonate or propylene carbonate to the electrolyte can improve the electrolyte ion transport performance and the interface impedance of the electrochemical device, the capacity retention rate of the electrochemical device is better, and the cycle thickness growth rate is lower. By regulating the composition and content in the electrolyte within the scope of protection of the present application, it is shown that the lithium-ion battery has better cycle performance.
[0138] In the electrolyte, the type and mass percentage of linear carbonates usually affect the cycle performance of the electrochemical device. It can be seen from Examples 2-7 to 2-10 that within the scope of protection of the present application, the addition of propyl propionate to the electrolyte improves the interfacial ion transport of the bulk phase as the mass percentage increases, the capacity retention rate of the electrochemical device becomes better, and the cycle thickness growth rate decreases. In Example 2-11, diethyl carbonate is added to the electrolyte to improve the overall ionic conductivity, the capacity retention rate of the electrochemical device is better, and the cycle thickness growth rate is lower. By regulating the composition and content in the electrolyte within the scope of protection of the present application, it is shown that the lithium-ion battery has better cycle performance.
[0139] In the electrolyte, the type and mass percentage of linear carboxylates usually affect the cycle performance of the electrochemical device. It can be seen from Examples 2-12 to 2-15 that within the scope of protection of the present application, propylene carbonate is added to the electrolyte. As the mass percentage increases, the interfacial ion transport of the bulk phase, the capacity retention rate of the electrochemical device becomes better, and the cycle thickness growth rate decreases. In Example 2-16, propyl acetate is added to the electrolyte to improve the overall ionic conductivity, the capacity retention rate of the electrochemical device is better, and the cycle thickness growth rate is lower. By regulating the composition and content in the electrolyte within the scope of protection of the present application, it is shown that the lithium-ion battery has better cycle performance.
[0140] Table 3
[0141]
[0142] The type and mass percentage of lithium salt additives usually affect the cycle performance of lithium-ion batteries. When lithium salt additives are further added to the electrolyte, and the type and content of the lithium salt additives are within the scope of protection of this application, the obtained lithium-ion battery has a higher cycle capacity retention rate and a lower cycle thickness growth rate. For example, in Example 3-1 to Example 3-3, due to LiBF 4 It can improve the battery interface, provide an interface rich in B elements, construct a multi-grain boundary (grain boundary ion transmission capacity is higher than bulk ion transmission capacity), enhance interface ion transmission, improve capacity retention rate, and at the same time, enhance positive electrode stability, inhibit gas production, and reduce cycle thickness growth rate. It can be seen from Examples 3-1 to 3-5 that the cycle performance of lithium-ion batteries is further improved.
[0143] It can be seen from Examples 3-6 to 3-8 that by adding propylene carbonate, ethylene carbonate, ethyl methyl carbonate and propyl propionate to the electrolyte and simultaneously adding a lithium salt additive, the electrochemical device has a higher cycle capacity retention rate and a lower cycle thickness growth rate.
[0144] Table 4
[0145]
[0146] The length of the separator beyond the positive electrode sheet usually affects the cycle performance of the lithium-ion battery. It can be seen from Examples 4-1, 4-3, and 4-5 that when the length of the separator beyond the positive electrode sheet is within the scope of the present application, as the length of the separator beyond the positive electrode sheet increases, the lithium-ion battery has a higher cycle capacity retention rate and a lower thickness growth rate. This is because the length of the separator beyond the positive electrode sheet increases, the overall area of the separator increases, the absorption of heat in the lithium-ion battery is enhanced, the overall battery temperature decreases, the gas production problem of the positive electrode is improved, and the cycle thickness growth rate is reduced, thereby further improving the cycle performance of the lithium-ion battery.
[0147] The thickness of the separator usually affects the cycle performance of the lithium-ion battery. From Example 4-2 to Example 4-4, it can be seen that when the thickness of the separator is within the range of the present application, as the thickness of the separator decreases, the lithium-ion battery has a higher cycle capacity retention rate, which can further improve the cycle performance of the lithium-ion battery.
[0148] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device comprising a negative electrode sheet and an electrolyte, wherein: The negative electrode plate comprises a negative electrode material layer, the negative electrode material layer comprises silicon element, and based on the total mass of the negative electrode material layer, the mass percentage A of the silicon element is 1% to 20%; The electrolyte comprises a compound of formula I and fluoroethylene carbonate: wherein R is selected from unsubstituted or fluorinated C2-C6 alkyl, unsubstituted or fluorinated C6-C 12 Aryl; Based on the total mass of the electrolyte, the mass percentage C of the compound of formula I is 3% to 50%.
2. The electrochemical device according to claim 1, wherein: The compound of formula I is selected from at least one of the following compounds: I-24。 3. The electrochemical device according to claim 1, wherein Based on the total mass of the electrolyte, the mass percentage B of the fluoroethylene carbonate is 5% to 30%.
4. The electrochemical device according to claim 1, wherein The relationship between the mass percentage B of the fluoroethylene carbonate and the mass percentage A of the silicon element satisfies 1≤B / A≤10.
5. The electrochemical device according to claim 1, wherein The relationship between the mass percentage C of the compound of formula I and the mass percentage A of the silicon element satisfies 1≤C / A≤10.
6. The electrochemical device according to claim 1, wherein The electrolyte further comprises a non-fluorinated cyclic carbonate, wherein the non-fluorinated cyclic carbonate comprises at least one of ethylene carbonate or propylene carbonate; Based on the total mass of the electrolyte, the mass percentage of the non-fluorinated cyclic carbonate is 10% to 30%.
7. The electrochemical device according to claim 1, wherein: The electrolyte includes linear carbonate, and the linear carbonate contains at least one of ethyl methyl carbonate and diethyl carbonate; based on the total mass of the electrolyte, the mass percentage of the linear carbonate is 5% to 40%.
8. The electrochemical device according to claim 1, wherein The electrolyte further comprises a linear carboxylate, which includes at least one of ethyl propionate, propyl acetate, propyl propionate, butyl acetate, ethyl butyrate or ethyl isobutyrate; based on the total mass of the electrolyte, the mass percentage of the linear carboxylate is 5% to 40%.
9. The electrochemical device according to any one of claims 1 to 8, wherein: The electrolyte includes a lithium salt additive, and the lithium salt additive includes at least one of lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, or lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide; Based on the total mass of the electrolyte, the mass percentage of the lithium salt additive is 0.1wt% to 5wt%.
10. The electrochemical device according to claim 1, wherein The electrochemical device comprises an isolation membrane. Along the extension direction of the electrode ear of the electrochemical device, the length of the isolation membrane beyond the positive electrode plate is a μm, the thickness of the isolation membrane is b μm, 0.0008≤b / a≤0.018, and a satisfies the condition: 1000≤a≤5000.
11. An electronic device comprising the electrochemical device according to any one of claims 1 to 10.
Citation Information
Cited By
Electrochemical apparatus and electronic apparatus comprising electrochemical apparatus
WO2026045436A1
Electrolyte and electrochemical device
WO2026183659A1